Spatial-temporal analysis of agricultural drought risk: insights from a Vietnam case study - Le, Tien; Sun, Qian (Chayn); Tran, Trinh Duc; Choy, Suelynn; Kuleshov, Yuriy (Frontiers in Earth Science, 2025)
A challenge in agricultural drought risk assessment is the lack of standardization for selecting indicators and aggregation methods, leading to inconsistent and less reliable outcomes. This issue is particularly evident in Vietnam, where diverse agricultural practices and regional climates add complexity to the assessment process. This study proposes a methodological framework specifically designed for Vietnam’s agricultural sector. It recommends the use of the Standardized Precipitation Index Vegetation Health Index and Soil Moisture (SM) for assessing drought hazards, while socioeconomic indicators such as agricultural land, population, Gross Domestic Product total income, agriculture-based income, literacy rate, and poverty rate are suggested for evaluating exposure and vulnerability. The research assesses drought risk across mainland Vietnam from 2015 to 2022, employing both equal proportion and Principal Component Analysis (PCA) to determine indicator weightings. The study highlights the advantages of Geographic Information System (GIS) and Remote Sensing data in evaluating drought risk across Vietnam. The result of spatiotemporal analysis shows that the drought hazard index varies significantly on a monthly basis, while exposure and vulnerability indices remain relatively stable over the years. During the examined period, 2015 and 2016 were identified as the years with the highest drought risk, followed by 2019 and 2020. The Mekong Delta, Central Highlands, and Northwest regions consistently exhibited high drought risk, reflecting their agricultural practices and socioeconomic vulnerabilities. This dynamic analysis provides critical insights for policymakers and stakeholders to proactively manage drought impacts in Vietnam’s agricultural sector.